The efficacy of adalimumab on experimentally induced spinal cord ischemia-reperfusion injury - Yasar Karatas; Mehmet Fatih Erdi; Bulent Kaya; Fatih Keskin; İbrahim Kılınç; Mehmet Uyar; Sabiha Serpil Kalkan; Emir Kaan Izci; Erdal Kalkan (Romanian Neurosurgery, 2020)
Objective: Paraplegia is a dangerous complication of thoracoabdominal aortic surgery. Various studies have been conducted on the prevention of this complication and some spinal cord protection methods have been proposed. However, there is not any modality that prevent the development of paraplegia certainly. In the I / R period, primary injury triggers secondary injury due to increased inflammation, apoptosis and free radical formation. In this study, we evaluated that the neuroprotective effect of adalimumab in spinal cord ischemia-reperfusion injury.